Ni-Bi-Zn ternary system investigation using diffusion couples technique - Gandova V.D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
An investigation of Ni-Bi-Zn system was performed using a diffusion couples technique and the diffusion paths were constructed. For that purpose diffusion couples consisting of solid Ni and liquid Bi-Zn phase were annealed at 450°C. The phase and chemical compositions of the contact zone were determined by scanning electron microscope. The diffusion layers found in the Ni-Bi-Zn ternary system were Beta1, γ-Ni5Zn21 and liquid. No intermetallic compounds in Bi-Ni binary phase diagram were observed.